Pengaruh Popularitas, Kualitas Argumen, Daya Tarik Pada Unggahan @Dr.Ziee di Tiktok Terhadap Kepercayaan, Sikap dan Niat Beli - Nisa Andini Faradina; Sri Hartini; Shafira Khairunnisa (Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
This research aims to determine the effect of popularity, quality of argument, attractiveness of @dr.ziee skincare product recommendation post on TikTok on trust, attitude and purchase intention by using cue utilization theory. This study uses a quantitative approach with the analytical technique used is partial least square with 200 respondents using TikTok who have a minimum age of 16 years and skincare users. The dependent variable used is the popularity of the post, the quality of the argument and the attractiveness of the post. The independent variable is purchase intention with the mediating variables are beliefs and attitudes. The results show that the popularity, argument quality and attractiveness of the post have a significant positive impact on trust which means that users take advantage of the popularity post, argumentation quality and attractiveness of the post to build on recommendation posts on social media. The attractiveness of post with short videos complements previous research using photo media, where the attractiveness of short videos can make consumers understand product information better because it is an information-rich medium compared to photos, thus affecting trust in recommendation posts. Trust in the recommendation post also affects attitudes and purchase intentions positively and significantly which is in accordance with previous research. Keywords: : Post Popularity; Argument Quality; Post Attractiveness; Trust; Attitude; Purchase Intention; Cue Utilization Theory